Systematic Investigation of Biomass Fatty Acid Productivity and CO2 Sequestration from Generator Gases by Fresh Water Microalgae in Photobioreactor for Biodiesel Application (Global Journal of Science Frontier Research, 2014)
The potential of microalgae as renewable energy feedstock for biofuel production is well recognized in developing countries and it is a large source of biomass for capturing CO 2 on non-arable lands. In the current studies photobioreactor with 2 L capacity was used and operated with generator exhaust gases for algal CO 2 sequestration. The reactor operated on generator exhaust gases with CO 2 ranges from 500-8000 ppm. As CO 2 concentration increased from 500 to 4000 ppm, there were steady increase in biomass 450 mg/l of dry weight till 2000 ppm, but above 2000 ppm there is decline in growth. The fatty acid profiles were more or less constant at all the CO 2 concentrations and maximum lipid content was 48%. The maximum reduction in CO 2 was 70% at 500 ppm whereas it was 52% at 4000 ppm. When CO 2 concentration increased to 8000 ppm without air, algae could not sustain and showed decline in biomass content. CO 2 fixation from generator gases not only reduces greenhouse gases but also help in getting fatty acid as biofuel.
Keywords: CO2 sequestration; biofuel; fatty acid; algae; generator gases; bench scale laboratory reactor